Integrasi Pasar Saham Kawasan Perdagangan Bebas Asean - China : Analisis Kointegrasi Pasar Saham Asean-5 plus China dan Implikasinya terhadap Pengelolaan Portofolio Internasional - Endri, Endri (International Research Journal of Business Studies, 2009)
This study examines the integration of stock markets integration among ASEAN-5 that is Indonesia, Malaysia, the Philippines, Singapore and Thailand plus China. Using daily data for the January 2, 2003 to December 31, 2009 period, the study employs the Johansen and Juselius multivariate cointegration procedures. In particular, this study considers whether the ASEAN-5 plus China markets are integrated or segmented using the time series technique of cointegration to extract long-run relations. The empirical results suggest that the ASEAN-5 plus China stock markets are cointegrated and are thus not completely segmented by national borders. However, there is only one cointegrating vector, leaving four common trends among the five variables. We therefore conclude that ASEAN-5 plus China stock markets are integrated in the economic sense, but that integration is far from complete. On a policy level, initiatives to further integrate the stock markets are feasible, and in fact desirable. From the perspective of the international portfolio investor, benefits of international portfolio diversification across the five markets are reduced but not eliminated.